How Music Tells a Story : Intertextuality in Stephen Chbosky's Novel The Perks of Being a Wallflower - Laitinen, Sohvi (My University, 2026)
This thesis examines the role of music as an intertextual element in Stephen Chbosky’s 1999 novel The Perks of Being a Wallflower. Focusing on thirteen songs included on a mix tape that the protagonist Charlie creates, this study analyzes how the songs interact with the novel’s narrative and reflect the protagonist’s life and emotional experiences. Drawing on theories of intertextuality by Julia Kristeva and Gérard Genette, this thesis argues that the songs function as expressive elements in Charlie’s life. The analysis and the songs are divided into three thematic sections – love and longing, trauma and grief, and healing and acceptance – which demonstrate how the songs mirror Charlie’s emotional development and story. The findings show that the songs contribute significantly to the novel’s narrative structure and themes as well as offer insight into Charlie’s identity formation and emotional journey.
Keywords: The Perks of Being a Wallflower, intertextuality, song lyrics, popular music, trauma, identity formation